Effect of physicochemical parameter on Cu (ll) ions adsorption by sulfuric acid treated spent grated coconut (Cocos nucifera) / Muhammad Yazid Misnan - Misnan, Muhammad Yazid (2015)
In this study, the spent grated coconut was treated with sulfuric acid has been used as an absorbent material to absorb low-cost Cu (II) in aqueous solution. Use adsorbent materials are preferred low cost compared with an absorbent material that is commonly used activated carbon because the price is expensive. Parameters examined in this study SSGC dose, pH, stirring rate, contact time and initial concentrations. The equilibrium data were analyzed using the Langmuir and the Freundlich isotherm. The kinetic process for the adsorption of Cu (II) ions onto SSGC were described by applying the pseudo-first-order and pseudo-second-order kinetic model. The Langmuir and Freundlich isotherms models were used in order to investigate the adsorption behavior of SSGC and the best fit to the data was obtained with the Langmuir isotherm model with maximum adsorption capacity (qmax) was found to be 192.30 mg g-I. So, it shows that adsorption process was monolayer with the coverage of the Cu (II) ions molecule only takes place at the outer surface of SSGC.